2022
DOI: 10.2147/jir.s353814
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Ratio of White Blood Cells as a Prognostic Predictor of Clostridioides difficile Infection

Abstract: A leukocyte count ≥15,000 cells/mL and serum creatinine of >1.5 mg/dL have been reported as two important predictors of severe CDI. However, the association of the differential ratios of blood leukocytes, and the prognosis of Clostridioides difficile infection (CDI) is not clear. Materials and Methods: A clinical study was conducted at medical wards of Tainan Hospital, Ministry of Health and Welfare in southern Taiwan between January 2013 and April 2020. Hospitalized adults (aged ≥20 years) with hospital-onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Another retrospective study found a link between neutrophilia and the greater possibility of CDI resolution 32 . Considering the diversity of the WBCs subpopulations in CDI patients, the total WBCs count may not be an accurate indicator of disease severity 33 . Though, the CDI severity was studied widely in another study and four different definitions of severity were discussed, the WBCs count (WBCs >15x10 9 /L) was a common predictor of the disease severity in three of them 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study found a link between neutrophilia and the greater possibility of CDI resolution 32 . Considering the diversity of the WBCs subpopulations in CDI patients, the total WBCs count may not be an accurate indicator of disease severity 33 . Though, the CDI severity was studied widely in another study and four different definitions of severity were discussed, the WBCs count (WBCs >15x10 9 /L) was a common predictor of the disease severity in three of them 16 .…”
Section: Discussionmentioning
confidence: 99%